High-efficiency thin-plate compression of multi-TW Ti:sapphire lasers - Li, Zhaoli; Zhou, Kainan; Mu, Jie; Wang, Xiaodong; Zeng, Xiaoming; Wu, Zhaohui; Wang, Xiao; Zuo, Yanlei (High power laser science and engineering, 2025)
Nonlinear compression experiments based on multiple solid thin plates are conducted in an ultra-high peak power Ti:sapphire laser system. The incident laser pulse, with an energy of 80 mJ and a pulse width of 30.2 fs, is compressed to 10.1 fs by a thin-plate based nonlinear compression. Significant small-scale self-focusing is observed as ring structures appear in the near-field of the output pulse at high energy. Numerical simulations based on the experimental setup provide a good explanation for the observed phenomena, offering quantitative predictions of the spectrum, pulse width, dispersion and near- and far-field distributions of the compressed laser pulse.